Effect of Lactobacillus plantarum PS128 on neuromuscular efficiency after a half-marathon - Yu, Chia-Hsien; Lai, Chang-Chi; Chen, Jing-Hsuan; Chen, I-Cheng; Tai, Hsia-Ling; Fu, Szu-Kai (Frontiers in Physiology, 2023)
Introduction:Lactobacillus plantarum PS128 (PS128) could be considered an antioxidant supplement to reduce muscle fatigue and improve exercise capacity recovery after vigorous exercise. Purpose: The purpose of this study is to investigate the effect of PS128 on muscle fatigue and electromyography (EMG) activity after a half-marathon (HM). Methods: The experimental design used a repeated-measures design with a double-blind approach. The participants either took two capsules of PS128 for 4 weeks as the PS128 group (PSG, n = 8) or took two capsules of a placebo for 4 weeks as the placebo group (PLG, n = 8) to ensure counterbalancing. The time points of the maximal voluntary isometric contraction (MVIC) and EMG activity test were set before probiotics were taken (baseline), 48 h before HM (Pre), and immediately at 0 h, 3 h, 24 h, 48 h, 72 h, and 96 h after HM. Results: EMG activity included median power frequency (MDF), integrated EMG (iEMG), and neuromuscular efficiency (peak torque/iEMG). The MVICs of knee extensors, analyzed by using an isokinetic dynamometer, showed a decrease from the Pre to 0 h (p = 0.0001), 3 h (p < 0.0001), 24 h (p < 0.0001), 48 h (p < 0.0001), 72 h (p = 0.0002), and 96 h (p = 0.0408) time points in the PLG. Sidak’s multiple comparisons tests showed that the PLG was significantly lower than the PSG at 0 h (p = 0.0173), 3 h (p < 0.0001), 24 h (p < 0.0001), 48 h (p < 0.0001), 72 h (p < 0.0001), and 96 h (p = 0.0004) time points. The MDF of vastus medialis oblique (VMO) in the PLG was significantly decreased 24 h after HM and significantly lower than that in the PSG at all times points after HM. The iEMG of VMO in the PLG was significantly decreased 48 h after HM and significantly lower than that in the PSG at 0 h, 3 h, 24 h, 48 h, and 72 h after HM. Conclusion: The PS128 supplementation may prevent the decrease in MDF, iEMG, and peak torque after vigorous exercise. Recreational runners may consider implementing a probiotic supplementation regimen as a potential strategy to mitigate muscle fatigue following HM.